Assessment of Municipal Solid Waste Management in Mymensingh City towards Sustainable and Profitable Waste Management - Khan, MN Hasan (Journal of Science and Technology Research, 2022)
Waste generation is increasing with the increasing of population at Mymensingh city but the waste management practice of the Mymensingh city corporation is not well established. The present study was conducted to find out profitable opportunities for municipal solid waste (MSW) management of Mymensingh city. Both primary and secondary sources were used to collect data as fulfillment of the study. Twenty two different locations of 5 wards in the city were visited for collecting these data. In the city estimated amount of waste produce 150 tons/day where 40-50% biodegradable and 15-25% recyclable paper, plastic, glass, metal etc. Currently waste is not being collecting and disposing scientifically due to unavailability of facilities, thus creating environmental pollution as well as unable to earn profit. Resource recovery and recycling could be a good option to reduce waste and earn profit from recyclable materials such as plastic, paper, metal etc. Besides this composting could be useful to produce bio fertilizer and bio gas from biodegradable wastes. By selling bio-fertilizer and biogas city could also earn profit. Integrated waste management combination with reduce, recovery, recycling and composting would be better solution for managing waste in the city. J. of Sci. and Tech. Res. 3(1): 41-48, 2021